KETERSEDIAAN ZAT GIZI MAKRO PADA MENU MAKAN SIANG YANG DISAJIKAN DI SEKOLAH DASAR ISLAM TERPADU (SDIT) INSAN MULIA KEDIRI TERHADAP KECUKUPAN ZAT GIZI ANAK SEKOLAH - Nur Fathin Sholihah; AASP Chandradewi; Ni Ketut Sri Sulendri; Luh Suranadi (Jurnal Gizi Prima (Prime Nutrition Journal), 2021)
Background : School-age children need balanced nutrition to  increase concentration and receive knowledge so that they can support learning activities. For this reason, it is necessary to provide lunch so that adequate nutrition is met. The purpose of this study was to analyze the availability of macro nutrients on the lunch menu presented in Insan Mulia Kediri's integrated Islamic elementary school (SDIT) towards the nutritional adequacy of school children. Method : This type of research used observational analytics from time including crosscestional research Methods of data collection using interviews, observation, and documentation. Sampling uses systematic random sampling technique with a sample of 216 students from a population of 442 students. Processing data using a distribution table and then presented in the form of tables and bar charts. Results : The provision of lunch menus by catering for 4 days, namely the average availability of macro-energy nutrients of 573 kcal, protein 15.3 grams, fat 7.0 grams, and carbohydrates 111.6 grams. The availability of energy is based on the adequacy of school children in more categories as many as 98 people (45.4%) and in the less category as many as 64 people (29.6%), Protein in the category of more than 101 people (46.8%), fat availability in the category there are 214 people (99.1%), and the availability of carbohydrates in the category is 151 people (69.9%). Conclusion : In general, the average availability of energy, protein, fat has fulfilled the adequacy of nutrition except fat. There is a significant relationship between the availability of macro nutrients and the nutritional adequacy of school children, which is 0.00 (p<0.05), so that the higher availability of macro nutrients is provided, the higher the nutritional adequacy of school children can be  fulfilled.